Sprachstrukturelle Modelle. Linguistische, spracherwerbsorientierte und didaktische Zugänge - Tophinke, Doris; Topalovic, Elvira; Rohlfing, Katharina J. (Mitteilungen des Deutschen Germanistenverbandes)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Raising Robotic Natives?: Persuasive Potentials of Social Robots in Early Education - Siebert, Scarlet; Tolksdorf, Nils Frederik; Rohlfing, Katharina J.; Zorn, Isabel (The Journal of Communication and Media Studies)

Do shy children behave differently than non-shy children in a child-robot interaction? An analysis of positive and negative expressions of shyness in kindergarten children - Tolksdorf, Nils Frederik; Dirk, Hönemann; Rohlfing, Katharina J.; Viertel, Franziska E.

When learning words with robots, children’s answers are multimodal: a challenge for a dialogue design - Tolksdorf, Nils Frederik; Mertens, Ulrich J.; Rohlfing, Katharina J.

Multimodale Kommunikation in frühen Buchlesesituationen und ihr Zusammenhang mit dem späteren Wortschatz. - Grimminger, Angela; Rohlfing, Katharina (Sprache · Stimme · Gehör)

Decontextualized talk in caregivers’ input to 12-month-old children during structured interaction. - Grimminger, Angela; Rohlfing, Katharina; Lüke, Carina; Liszkowski, Ulf; Ritterfeld, Ute (Journal of Child Language)

Utilizing Pragmatic Frames as an analytical tool for children’s performance during word learning. - Rohlfing, Katharina; Grimminger, Angela (Proceedings of the 9th Joint IEEE International Conference on Development and Learning and on Epigenetic Robotics)

Does emotional narrative context influence retention of newly learned words? - Rohlfing, Katharina; Nachtigäller, Kerstin; Berner, Anna; Foltz, Anouschka (Narrative, Literacy and Other Skills. Studies in intervention.)

Language learning from the use of gestures. - Rohlfing, Katharina (International Handbook of Language Acquisition)

Frühe Sprachentwicklung - Rohlfing, Katharina

Evidence for Early Comprehension of Action Verbs - Nomikou, Iris; Rohlfing, Katharina; Cimiano, Philipp; Mandler, Jean M. (LANGUAGE LEARNING AND DEVELOPMENT)
Applying an eye-tracking technique, we tested early verb understanding in 48 infants aged 9 and 10months. Infants saw two objects presented side by side and heard a verb that referred to a common action with one of these objects (e.g., eating relating to a banana). The verbs were spoken by the parent in an interrogative manner in order to elicit a looking behavior in the infant. Results showed that 9-month-old infants did not show recognition of our test words. However, 10-month-old infants were able to understand a number of the tested verbs. In the discussion, we relate our findings to the nature of early verb representations.

The timing of pointing-speech combinations in typically developing and language-delayed toddlers. - Grimminger, Angela (Proceedings of the 6th Gesture and Speech in Interaction)

Die Integration von Lautsprache und Gesten in Lernkontexten. - Grimminger, Angela (Mitteilungen des Deutschen Germanistenverbandes)

Wie können Studierende des Lehramts an Grund- und Förderschulen auf das kooperative Arbeiten in der inklusiven Grundschule vorbereitet werden? Posterpräsentation auf der 7. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Entwicklung kooperativen Arbeitens bei Lehramtsstudierenden für den naturwissenschaftlichen Sachunterricht in der inklusiven Grundschule. Posterpräsentation auf dem 8. Paderborner Grundschultag - Löper, Marwin Felix; Görel, Gamze; Hoya, Fabian Karl; Kirsch, Alexander; Mester, Theresa; Schulze, Jan Roland; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Kooperatives Unterrichten von Studentinnen und Studenten des Lehramts an Grund- und Förderschulen im naturwissenschaftlichen Sachunterricht. Eingeladener Vortrag in der Naturwissenschaftlichen Fakultät der Leibniz Universität Hannover. Institut für Didaktik der Naturwissenschaften - Hellmich, Frank; Schulze, Jan Roland

Feedback im Leseunterricht der Grundschule aus der Perspektive von Kindern und Lehrkräften – Befunde aus einer Mehrebenenanalyse. Vortrag im Symposium „Qualität von Leseunterricht – Determinanten und Effekte“ (Chairs: Annika Ohle-Peters & Nele McElvany) auf der 7. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hoya, Fabian Karl; Hellmich, Frank

Prerequisites for children’s attitudes towards peers with special educational needs. Paper Presentation. Symposium: “Escúchame! Listen to me! Exploring under-served students’ voice through innovative and participatory research designs“ (Chair: Christoforos Mamas). AERA (American Educational Research Association) - Hellmich, Frank; Löper, Marwin Felix

Auswirkungen eines Trainings zum kooperativen Arbeiten auf die Selbstwirksamkeitsüberzeugungen von Studierenden in Bezug auf den inklusiven Grundschulunterricht. Vortrag auf der 7. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Görel, Gamze

Prerequisites of Primary School Students’ Pro-social Behavior in the Inclusive Classroom. Single Paper. 18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Löper, Marwin Felix; Hellmich, Frank

Individual and Institutional Determinants for Primary School Teachers’ Self-Efficacy Beliefs regarding Inclusive Education – Results from Qualitative Interviews. Individual Oral Presentation. Porto International Conference on Research in Education (ICRE) - Hellmich, Frank; Löper, Marwin Felix; Knickenberg, Margarita

Children’s Pro-social Behavior towards Peers with Social or Emotional Disabilities in the Inclusive Classroom. Individual Oral Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hellmich, Frank

Under which conditions does the social participation of students with special educational needs succeed? Keynote. Conference "Inclusive Education – Giving students a voice" - Hellmich, Frank

Effekte eines Trainings zum kooperativen Arbeiten im inklusiven Unterricht auf die Selbstwirksamkeitsüberzeugungen von Studierenden des Lehramts an Grund- und Förderschulen. Vortrag auf der 10. Tagung der Sektion Empirische Bildungsforschung in der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE)/ Arbeitsgruppe Empirische Pädagogische Forschung (AEPF)/ Kommission Bildungsorganisation, Bildungsplanung, Bildungsrecht (KBBB)/ Thema: „Gesellschaftliche Entwicklungen als Herausforderungen für empirische Bildungsforschung“ - Schulze, Jan Roland; Hoya, Fabian Karl; Hellmich, Frank

Selbstwirksamkeitsüberzeugungen von Lehramtsstudierenden und Erfahrungen aus dem inklusiven Unterricht in der Grundschule. Posterpräsentation auf der 10. Tagung der Sektion Empirische Bildungsforschung in der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE)/ Arbeitsgruppe Empirische Pädagogische Forschung (AEPF)/ Kommission Bildungsorganisation, Bildungsplanung, Bildungsrecht (KBBB)/ Thema: „Gesellschaftliche Entwicklungen als Herausforderungen für empirische Bildungsforschung“ - Franzen, Katja; Görel, Gamze; Hoya, Fabian Karl; Filipiak, Agnes; Albers, Timm; Hellmich, Frank

Effects of a Training to Foster Pre-Service Teachers’ Knowledge about Team-Teaching on their Competencies for Inclusive Education at Primary School. Single Paper. ECER 2019 (European Conference on Educational Research). “Education in an Era of Risk – the Role of Educational Research for the Future“ - Schulze, Jan Roland; Hoya, Fabian Karl; Hellmich, Frank

Potential Influencing Factors for Teachers’ Self-Efficacy Beliefs concerning Inclusive Education. Single Paper.18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Hellmich, Frank; Löper, Marwin Felix; Knickenberg, Margarita

The Role of Pronounced and Perceived Parental Feedback on Children’s Reading Comprehension. Single Paper. 18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Hoya, Fabian Karl; Hellmich, Frank

Primary School Teachers’ Personal Resources and the Quality of Inclusive Learning Processes. Single Paper. 18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Görel, Gamze; Hellmich, Frank

Prerequisites for Primary School Teachers’ Intentions and Everyday Day Practices concerning Inclusive Education. Single Paper. ECER 2019 (European Conference on Educational Research). “Education in an Era of Risk – the Role of Educational Research for the Future“ - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Development Of Preservice Teachers' Inclusive Competences. The "KinU"-Project. Poster Presentation. ECER 2019 (European Conference on Educational Research). “Education in an Era of Risk – the Role of Educational Research for the Future“ - Franzen, Katja; Görel, Gamze; Filipiak, Agnes; Albers, Timm; Hellmich, Frank

Einstellungen und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften in Bezug auf den inklusiven Unterricht als Determinanten für ihren intentionalen Umgang mit Heterogenität im Klassenzimmer. Vortrag auf der 10. Tagung der Sektion Empirische Bildungsforschung in der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE)/ Arbeitsgruppe Empirische Pädagogische Forschung (AEPF)/ Kommission Bildungsorganisation, Bildungsplanung, Bildungsrecht (KBBB)/ Thema: „Gesellschaftliche Entwicklungen als Herausforderungen für empirische Bildungsforschung“ - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule. Posterpräsentation. Symposium der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF). Transfer, Nutzung und Relationen von Wissenschaft und Praxis in den Bildungsbereichen - Schulze, Jan Roland; Hoya, Fabian Karl; Kirsch, Alexander; Brandenburg, Melanie; Schwab, Susanne; Hellmich, Frank

Kompetenzentwicklung im inklusiven Unterricht: Förderung der Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Systeme. Posterpräsentation. Symposium der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF). Transfer, Nutzung und Relationen von Wissenschaft und Praxis in den Bildungsbereichen - Franzen, Katja; Görel, Gamze; Filipiak, Agnes; Albers, Timm; Hellmich, Frank

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag. Symposium der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF). Transfer, Nutzung und Relationen von Wissenschaft und Praxis in den Bildungsbereichen - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland

Möglichkeiten der Förderung der Selbstwirksamkeitsüberzeugungen von Lehramtsstudierenden durch Erfahrungen aus dem inklusiven Unterricht in der Grundschule. Posterpräsentation auf der 54. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik und Bildungsforschung – Fremde Schwestern?“ - Franzen, Katja; Görel, Gamze; Hoya, Fabian Karl; Filipiak, Agnes; Albers, Timm; Hellmich, Frank

Auswirkungen einer Lerneinheit zum kooperativen Arbeiten auf die Selbstwirksamkeit von angehenden Grund- und Förderschullehrkräften in Bezug auf den inklusiven Unterricht. Vortrag auf der 54. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik und Bildungsforschung – Fremde Schwestern?“ - Schulze, Jan Roland; Hoya, Fabian Karl; Hellmich, Frank

Determinanten für die Einstellungen von Grundschulkindern gegenüber Peers mit einem sonderpädagogischen Förderbedarf in der emotionalen und sozialen Entwicklung. Vortrag auf der 54. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik und Bildungsforschung – Fremde Schwestern?“ - Löper, Marwin Felix; Hellmich, Frank

Kompetenzprofile pädagogischen Wissens. Ein Blick auf die Entwicklung Theologistudierender im Praxissemester. - Caruso, Carina; Seifert, Andreas (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Controllable high-speed polariton waves in a PT-symmetric lattice - Ma, Xuekai; Kartashov, Yaroslav Y; Gao, Tingge; Schumacher, Stefan (New Journal of Physics)

»Eine Aufnahme, wie sie wohl selten Künstlern zu Theil wird«: Clara Schumann in Detmold - Grotjahn, Rebecca (ad notam. Jahrbuch der Hochschule für Musik Detmold)

The network ROI - Khan, Gohar; Mohaisen, Manar; Trier, Matthias (Internet Research)
Purpose Leveraging social action theory, social network theory and the notion of network externality, the purpose of this paper is to model two different return on investment (ROI) measures: the networked ROI which captures the network effect originating from a social media investment, and the discrete ROI which focuses social media discrete returns from individual users. Design/methodology/approach A field experiment was set up over a period of three months to test the effects of two variants of an advertisement campaign (a social vs a discrete ad) on the modeled networked and discrete ROIs. Findings The authors find that emphasizing discrete user actions leads to lower network gains, but higher monetary returns while the social action emphasis produces higher network gains, but lower monetary returns. The study further suggests that social action focus is preferable for brand promotion and engagement, whereas the discrete action focus is suitable for boosting sales and website traffic. Practical implications Several potential implications for social media researchers and marketers are also discussed. Originality/value The authors for the first time showed that that the social media returns are derived not only from individual actions taken by the user (e.g. likes and shares) but also from users’ social interdependencies and the additional exposure that results from network effects.
Keywords: Economics and Econometrics; Sociology and Political Science; Communication

Einleitung: Zugänge zur Kinderladenbewegung - Bock, Karin; Göddertz, Nina; Heyden, Franziska; Mauritz, Miriam (Zugänge zur Kinderladenbewegung)
Dieser Sammelband ist ein Ergebnis aus unserem Forschungszusammenhang „Die Kinderladenbewegung: Biographische Auswirkungen und gesellschaftspolitische Einflüsse institutioneller Erziehungsarrangements“, der uns seit 2011 als Nachwuchsforscherinnengruppe der Hans-Böckler-Stiftung verbindet. Aus diesem Forschungszusammenhang sind mehrere Veröffentlichungen hervorgegangen, darunter drei Dissertationen (Göddertz 2018; Heyden 2018; Mauritz 2018), ein Handbuchartikel (Göddertz und Bock 2018), ein Aufsatz in einem Sammelband (Bock et al. 2018), drei Aufsätze in Zeitschriften (Bock und Schäfer 2010; Göddertz und Mauritz 2018; Heyden und Mauritz 2018) und drei Lexikon-Artikel (Bock et al. 2015 a-c).
Keywords: Erziehungsarrangements; Kinderladenbewegung; Pädagogik

Zugänge zur Kinderladenbewegung
Das Buch gibt einen umfassenderen Einblick in die historischen, theoretischen und praktischen Zugänge zur Kinderladenbewegung. Damit wird die Kinderladenbewegung nicht nur als ‚Nebenerscheinung‘ der Studentenbewegung begriffen, sondern im Kontext von Frauen-, Studenten- und Erziehungsbewegung als eigenständige Soziale Bewegung gewürdigt.
Keywords: Bildungswissenschaft Geschichte Frauenbewegung Kindergarten Theodor W. Adorno Erziehung nach Auschwitz Kritische Theorie Kritische Erziehungswissenschaft

Efficient C-band single-photon upconversion with chip-scale Ti-indiffused pp-LiNbO3 waveguides - Xie, Zhenda; Luo, Kai Hong; Chang, Kai Chi; Panoiu, Nicolae C.; Herrmann, Harald; Silberhorn, Christine; Wong, Chee Wei (Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Robust Improper Signaling for Two-user SISO Interference Channels - Soleymani, Mohammad; Lameiro, Christian; Santamaria, Ignacio; Schreier, Peter J (IEEE Trans. Commun.)

Ergodic Rate for Fading Interference Channels with Proper and Improper Gaussian Signaling - Soleymani, Mohammad; Santamaria, Ignacio; Lameiro, Christian; Schreier, Peter J (Entropy)

Energy-efficient Design for Underlay Cognitive Radio Using Improper Signaling - Soleymani, Mohammad; Lameiro, Christian; Schreier, Peter J; Santamaria, Ignacio (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Rate Analysis of SC-FDE and OFDM Systems with Low Resolution ADCs - Soleymani, Mohammad; Maham, Behrouz (Proc. IEEE 30th Annual International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC))